Active Ageing Index in Korea – Comparison with China and EU countries. Issue 1 (17th February 2019) - Um, Jinpil; Zaidi, Asghar; Choi, Sung‐Jae
Abstract: The evidence‐based policymaking relies on the use and robustness of the available data. Many conceptual and operational difficulties restrict this process, not least in making use of evidence to identify policy priorities. The Active Ageing Index (AAI), developed originally for the 28 European Union countries, offers a strong motivation in this respect. This paper reports on the development of the AAI for Korea, a country where speed and level of population aging is among the highest in the world. Drawing on the comparative analysis of the AAI results for Korea, China, and European countries, we find that Korea's AAI (35.3) is higher than the average of the AAI for all EU countries (33.9) but lower than China (37.3). Fitting Korea into the overall ranking with the EU countries and China (ranked 7), Korea is ranked 11, just behind Germany (10). The AAI results in Korea show that the employment domain performs extremely well compared with the EU countries, but other domains, especially "Social participation" and "Independent, healthy and secure living, " are achieving less favorable outcomes. High employment among the current cohorts of older workers in Korea can be attributed largely to the constraints of low pension income status.